#### Answer

$f(x,y) =\dfrac{x^2}{y} -\dfrac{1}{y}+C$

#### Work Step by Step

We have:$M=\dfrac{2x}{y}; N=\dfrac{1-x^2}{y^2}; P=0$
and $\dfrac{\partial N}{\partial z}=\dfrac{\partial P}{\partial y}=0\\ \dfrac{\partial M}{\partial z}=\dfrac{\partial P}{\partial x}=0 \\ \dfrac{\partial N}{\partial x}=\dfrac{\partial M}{\partial y}=\dfrac{-2x}{y^2}$
This implies that $F$ is conservative, so $F =\nabla f$
Thus, $ \dfrac{\partial f}{\partial x}=\dfrac{2x}{y} $
$\implies f =\dfrac{x^2}{y} +k (y) ...(1)$
$\dfrac{\partial f}{\partial y}=\dfrac{1-x^2}{y}=\dfrac{-x^2}{y}+\dfrac{dk}{dy}$
$\implies \dfrac{ dk}{dy}=\dfrac{1}{y^2} \\k(y) =\dfrac{-1}{y} +C ...(2)$
From equations (1) and (2), we have: $f(x,y) =\dfrac{x^2}{y} -\dfrac{1}{y}+C$